Job Satisfaction and Women’s Turnover Intentions in Pakistan’s Public Universities - Aliya Bushra (The Lahore Journal of Business)
The aim of this study is to test the impact of women’s job satisfaction on their turnover intentions, specifically for those employed in the education sector. Using a sample drawn from two different universities in Lahore, Pakistan, we measure their levels of job satisfaction by evaluating their general working conditions, pay and potential for promotion, professional relationships, use of skills and abilities, and activities assigned. We find that flexible working hours, workplace location, performance appraisal, and skills utilization have a highly positive significance on turnover intentions, while professional autonomy, job security, and promotion have an inverse impact on job satisfaction and turnover intentions.